LIVING QUR’AN DALAM TRADISI PEMBACAAN SURAH AL-INSHIRĀH DI LEMBAGA TAMAN PENDIDIKAN IHYAUL ULUM CANGAAN GRESIK - Kurnia Wahidah; Ahmad Saddad (UIN Siber Syekh Nurjati Cirebon, 2024)
This research examines the tradition of reciting Surah Al-Inshirāh at the Ihyaul Ulum Education Park Institution in Cangaan, Gresik Regency, from the perspective of Living Qur'an. The study aims to reveal the